Additional diagnostic value of digital radiology in plantar fasciitis diagnosis (Faculty of Medicine Universitas Indonesia, 2017)
Background: Ultrasonography (USG) is regarded as the gold standard to differentiate normal plantar fascia and plantar fasciitis. Conventional radiography or plain X-ray is typically used to exclude differential diagnosis. Lately, conventional radiography has been digitalized and leads to better visualization of the soft tissue. However, it is not known whether digital radiography evaluation for calcaneus area, both qualitative and quantitative, has a similar diagnostic value as USG findings. Therefore, this study aimed to evaluate whether there is a strong correlation between digital radiographic and USG findings for diagnosing plantar fasciitis.Methods: This is a cross sectional study examining adult patients (>18 years old) presenting with inferior heel pain. Plantar aponeurosis thickness was measured by digital radiography and ultrasonography; measurement was performed three times in each modality, and the average value was recorded. Fat stranding, presence of calcaneal enthesophyte, and microfracture were also evaluated in digital radiography. Measurement results were classified into plantar fasciitis diagnosis using the cut-off value 4 mm.Results: There was no significant correlation between plantar aponeurosis thickness measured by digital radiography and by ultrasonography (r=0.069, p=0.688). There was no significant association between plantar fasciitis diagnosis by digital radiography and ultrasonography (p=0.162). However, digital radiography showed good sensitivity to detect plantar fasciitis using a cut-off value of >4 mm plantar fascia thickness.Conclusion: Digital radiography might be used to aid definitive diagnosis for plantar fasciitis.